IMPROVING STUDENTS' READING COMPREHENSION OF RECOUNT TEXT BY USING THINK-PAIR-SHARE (TPS) TECHNIQUE - Vidya, Radhita; Nuraini, Annisa (PROJECT (Professional Journal of English Education), 2019)
The aims of this research is to improve reading comprehension of the eighth-grade students using think-pair-share technique. The researchers applying this technique is to make students actively learn in classthrough pair discussions and sharing information with their friends. The researchers used a classroom action research (CAR) method, this research has been carried out in three cycles to achieve students improvement in reading comprehension. The mean scores of students in the first cycle is 57.60, in the second cycle is 64.67, and in  the third cycle is 77.20. The mean scores of the three cycles prove that the think-pair-share technique has succeeded in improving students' reading comprehension of recount text. Keywords: Think-Pair-Share, Reading comprehension ,Recount text.